Mild Anemia May Affect Thyroid Function in Pregnant Chinese Women During the First Trimester - Nie, Guan-ying; Wang, Rui; Liu, Peng; Li, Ming; Sun, Dian-jun (Frontiers in Endocrinology, 2021)
Background: Pregnant women are very susceptible to anemia, which can damage the thyroid. However, insufficient attention has been paid to mild anemia. The purpose of this study is to explore the effect of mild anemia on the thyroid function of pregnant women in the first trimester. Methods: 1761 pregnant women in the first trimester were enrolled from Shenyang, China, and divided into mild anemia group and normal control group according to hemoglobin levels. TSH, FT4 and FT3 were compared among the two groups. Results: The TSH level of pregnant women with mild anemia was higher than that of pregnant women without mild anemia (P<0.05). We only chose normal control women to set new reference intervals for TSH, FT3 and FT4 in the first trimester, which were 0.11–4.13 mIU/L, 3.45–5.47 pmol/L and 7.96–16.54 pmol/L, respectively. The upper limit of TSH 4.13 mU/L is close to the upper limit 4.0 mU/L from 2017 ATA guideline, indicating that exclusion of mild anemia may reduce the difference in reference values of different regions. Mild anemia is related to 4.40 increased odds of abnormally TSH (95% CI: 2.84, 6.76) and 5.87 increased odds of abnormal FT3 (95% CI: 3.89, 8.85). The proportion of hypothyroidism and subclinical hypothyroidism in patients with mild anemia was higher than that in those without anemia (0.6% vs. 0, P =0.009；12.1% vs. 1.9%, P <0.001). Conclusions: Mild anemia may affect thyroid function in first trimester, which highlights the importance of excluding mild anemia confounding when establishing a locally derived specific reference interval for early pregnancy.